Porcine Reproductive and Respiratory Syndrome Virus Type 1.3 Lena Triggers Conventional Dendritic Cells 1 Activation and T Helper 1 Immune Response Without Infecting Dendritic Cells - Bordet, Elise; Blanc, Fany; Tiret, Mathieu; Crisci, Elisa; Bouguyon, Edwige; Renson, Patricia; Maisonnasse, Pauline; Bourge, Mickael; Leplat, Jean-Jacques; Giuffra, Elisabetta; Jouneau, Luc; Schwartz-Cornil, Isabelle; et al. (Frontiers in Immunology, 2018)
Porcine Reproductive and Respiratory Syndrome virus (PRRSV) is an arterivirus responsible for highly contagious infection and huge economic losses in pig industry. Two PRRSV genotypes have been identified: the genotype 1 from European origin and the genotype 2 from North American origin. Genotypes 1 have been further divided into four subtypes. Genotype 1 subtype 3 (type 1.3) such as Lena are more pathogenic than type 1.1 such as Lelystad or Flanders13. One main feature of all PRRSV strains is their capacity to delay the appearance of neutralizing antibodies, leading to a viremia that can last several months. The role of the cellular immune response in PRRSV clearance remains ill defined, with type 1.3 viruses triggering a higher Th1 response than type 1.1 without striking differences in the viremia time course. It has been proposed that the inability of pigs to achieve rapid sterilizing immunity upon PRRSV infection might rely on the virus capacity to infect and inhibit dendritic cells (DCs) functions, as it has been observed for in vitro differentiated monocytes derived DCs (moDCs). The higher pathogeny of type 1.3 viruses compared with type 1.1 may also result from their differential ability to infect and/or activate DCs. However, the interactions of PRRSV with in vivo-differentiated-DC subtypes such as conventional DC1 (cDC1), cDC2 and moDCs have never been investigated. Here, the capacity of type 1 (Lelystad, Flanders13 and Lena) to infect DCs and to trigger differential T helper responses were compared. None of these 3 strains infected DCs neither in vivo nor in vitro. Moreover, Lena, but not LV and FL13, triggered cDC1 activation paralleled by a strong Th1 response. We thus propose that the ability of all PRRSV strains to alter the immune response is not due to the DCs infection or direct DCs inhibition.